"Be/coming" White and the Myth of White Ignorance: Identity Projects in White Communities. Issue 3 (26th May 2016) - Moon, Dreama G.
Abstract : Communication studies of White enculturation practices are almost nonexistent despite the centrality of discursive fields in building Whiteness as an embodied way of life. The process of becoming White is investigated via exploration of racial enculturation practices. Data are 124 racial epiphany stories of Whites responding to the question: "When was the first time you became aware that you had a race and what that meant?" Two themes emerged: Performances of Whiteness by Family/Friends and Public Performances of White Privilege.